Resenlund og Brøndumgård bronzedepoter – Kult og samfund i yngre bronzealder - Varberg, Jeanette (Kuml, 2005)
The bronze deposits from Resenlund and Brøndumgård In the Late Bronze Age, bronze deposits in fields and bogs constitute a large part of the archaeological material. Huge values were deposited in the ground during this period, and the archaeological material witnesses a wide-ranging custom of sacrifice. The deposits are therefore central to the understanding of the societies, which once left their items in the ground, and new finds contribute to a more varied impression of the picture already existing of the Late Bronze Age. This article presents two hitherto unpublished deposits from the Early Bronze Age, both from Northern Jutland. These deposits contain bronze objects, which may throw new light on the ritual practice of the North Jutland society and its social identity during period IV (1100 BC - 900 BC). The composition of the Brøndumgård depot is special in that it contains part of hitherto unknown artefacts. The depot consists of a belt plate, fragments of at least two cuff-shaped bracelets, fragments of three mounts, a bronze ring, a sickle, two four-spoke wheel pendants, an eight-spoke wheel pendant, part of a neck ring with the head of a horse, and five bronze nuggets. The belt plate and fragments of a cuffshaped bracelet date the find to period IV. The decorations on the eight-spoke wheel pendant and the mounts also point towards period IV. The dating of the find is thus hardly questionable. The Brøndumgård depot was probably buried in a double- conic earthenware pot. The deposit was found at the bottom of a ridge originally marking the border of a wetland area. Several prehistoric mounds are preserved on top of the ridge. The location of the find – in a border area between firm ground and wetlands – indicates that the deposit should probably be interpreted as a wetland sacrifice; a gift to the gods at the edge of a bog, which was considered a magical gateway between the world of the humans and the supernatural during large parts of prehistory. The original use of the mounts is difficult to determine. Their form does not indicate a use as bucket mounts. Harness plates are another possibility, but so far, such horse mounts are not known from other finds. The bronze may have been fixed to the leather armour of a warrior, but no other finds support this theory. As a last suggestion, the mounts may have been fixed to the body of a carriage. The bronze ring supports this assumption. Apart from rings, the carriage mounts known from the Urnemark and Hallstatt Cultures include oblong, ornamented metal plates similar to the mounts from the Brøndumgård depot. It should be stressed that these are not imported mounts, as the decoration is very similar to the decoration occurring on the cuffshaped bracelets, which are considered a local Jutland product. Thus, cult wagons probably existed during the Late Bronze Age in Scandinavia. The question is: to what extent, and when? Already during the Early Bronze Age, the Trundholm Sun Chariot from Northern Zealand and the two-wheeled chariot from the rock carvings at Kivikgrav in South-eastern Scania indicate that the wagon had a central function in the iconography of the Early Bronze Age. We just lack finds of wagon parts in the archaeological material from the period to tell whether the pictorial representations of the Early Bronze Age reflect actual events. The use of wagons for ceremonies and cult processions can therefore probably not be compared to the Central European Urnemark Culture’s influence on Northern Europe until the Late Bronze Age. It is thus not until the emergence of the Urnemark Culture that the wagon plays a visible part in Central European cult. Here, the wagons are known from several well-preserved graves, which provide fine possibilities for reconstructing the look and function of the wagons. As a rule, the wagons have four wheels and a rather small body, which would have made them unsuitable for the transportation of large, heavy wagonloads. Furthermore, the body is decorated with metal plates. The rich ornamentation combined with the small, unpractical size and the fact that they were used as grave goods in rich graves all indicate that the wagons were used for processions connected to the Central European cult. In Denmark, we have but a few complete finds of wagon plates from the Bronze Age. In the absence of such complete metal plate finds, it is much more difficult to recognize metal plates as part of possible wagon ornaments. It is therefore necessary to intensify the attention concerning plates and other metal items, which may have been riveted onto wood. If such plates are found in connection with horse equipment, which naturally often occur in the same context as wagon parts, this may considerably strengthen their interpretation as wagon plates. Perhaps the eight-spoke wheel pendant should be interpreted as part of a horse’s equipment? Maybe as some sort of horse harness jingles attached to the bridle – although the eye for hanging seems too small compared with other finds of definite horse bridle jingles. In stead, the wheel pendant could have been attached to another part of the harness. The four-spoke type of wheel pendant has not previously been found in Scandinavia, but in a much larger version it is known from the Period II- grave from Tobøl in Western Jutland. The wheel with four spokes is also known from the Early Bronze Age iconography. As a pendant, the wheel with four spokes is a phenomena first occurring in Northern Europe at the same time as the Urnemark Culture begins to influence the form of objects in the Late Bronze Age. Probably, the four-spoke wheel – like the eight-spoke wheel – is from a horse’s harness. In Northern Europe, several deposits combining women’s jewellery and horse equipment are known from period V. The fact that these two artefact types are often found together in the deposits may reflect a fixed practice of some ceremony or cult act. Perhaps the deposits are really elements from a ceremonial procession – in which the wagon played a prominent part – sacrificed to the supreme beings. In the Brøndumgård depot, the women’s jewellery and horse equipment is even supplemented by possible wagon plates, and the find thus supports the hypothesis presented above that the ceremonial procession included women, horses, and a wagon. Women’s jewellery and the horse and wagon equipment were probably made by the same bronze caster, and perhaps the objects were meant to be a complete ceremonial outfit for a woman and a wagon. In the Bronze Age, it was not an unknown phenomenon that special jewellery sets were made as a complete whole, and it is therefore not altogether impossible that a complete set of equipment for a woman and a wagon were made by the same craftsman. Perhaps the depot is even containing the remains of a priestess’ equipment, ceremonial wagon included? In this respect, the Roman writer Tacitus’ retelling of the myth concerning the fertility cult of the goddess Nerthus is especially interesting – in spite of the fact that the myth was written down almost 1000 years later than the dating of the Brøndumgård depot. The horse-drawn chariot is central in Tacitus’ account, as each year, somewhere in the northern part of the free Germania, a procession with Nerthus in a horse-drawn ceremonial chariot passed from village to village to announce the coming of spring and fertility. The myth shows that the tradition of a ceremonial chariot was probably predominant in Northwest Europe during the Early Iron Age. It is therefore not unlikely that the ceremonial chariot, perhaps driven by a priestess, was part of the ritual practice in Jutland during the Late Bronze Age, and that it remained a strong tradition until the Early Iron Age. The Resenlund depot consists of three spiral arm rings, two sickles, a double button, three fragments of cuff-shaped bracelets, three parts of neck rings, a socketed spear head, a dress pin, a bronze celt, and part of a sword blade. All artefacts were probably of Scandinavian origin, possibly from the area around the Limfjord. It is not always possible to determine whether the depot was placed in a container, for instance a clay vessel. Several of the items were ruined prior to being deposited, whereas others were old and worn. The depot was probably deposited in the course of the Bronze Age period IV, between 1100 and 900 BC, as quite a few of the items date from this time. The depot thus comprises many different artefact types, and both weapons, women’s jewellery, and tools are represented. From the composition, the depot may be interpreted as a sacrifice representing a cult act managed by one or more wealthy peasants connected with arable land. The wear marks on the jewellery probably indicate that they were inherited items that may have been in the family’s possession for generations, before they were handed over to the ground. The depot itself may be interpreted as a sacrifice to the superior beings, perhaps to thank for success and fertility. At the same time, the sacrificial act itself may have helped support the position of the leading families in the local community. The two deposits from Resenlund and Brøndumgård were both deposited within the same area near the Limfjord between 1100 and 900 BC, and they both contain items with a form and an ornamentation specifically characteristic for this particular area. Both deposits were found in connection with water or wetlands, as is characteristic of the sacrificial practice of the Late Bronze Age culture in Scandinavia. However, the composition and context in the two deposits differ, and so the two finds tell individual stories. The composition of the Resenlund depot makes it interpretable as a sacred depot, with numerous different artefacts representing one or more peasant families. In favour of this interpretation is the fact that the depot contains items belonging to more women and at least one man, as well as a sickle, which may indicate that the sacrifice was connected to agriculture and fertility. The Brøndumgård depot may be part of a ritual procession sacrificed to the supreme beings. The women’s jewellery and horse and wagon equipment were probably made by the same bronze caster, and perhaps the items were meant as a complete ceremonial outfit for a priestess and her chariot. The Resenlund depot may reflect the cult act of one peasant family, which perhaps included people from a small neighbourhood – as opposed to the Brøndumgård depot, which may have been the remains of a ceremonial procession including a larger number of people. The deposits may thus be the result of two different ceremonies and cult acts made by different groups of society, but probably within the framework of the same fertility cult and practice of ritual sacrifice. Period IV of the Bronze Age was a very innovative era as regards the creation of new artefact types. Many new variants of women’s jewellery and other ornaments turn up in this period only to disappear again from the find material in period V. The variations within the ornaments are especially expressed within North and Central Jutland, to which a large number of artefacts are specific within period IV. They are artefact types, which were almost solely used in Jutland, and in this respect, this area differs from the rest of Scandinavia. Fig. 18 shows the artefacts that Evert Baudou considers special Jutland types, such as the specially ornamented bone buttons and pendants found in large numbers in graves in the Mid-Jutland area. To these special Jutland types, I would like to add the three wheel pendants from the Brøndumgård depot, which – with the five wheel pendants from the Sæsing depot – also constitute a special Jutland type during Period IV. The characteristics of the Jutland artefact types made Baudou suggest that judging from the unique artefact types in Jutland, we could be dealing with two tribal groups in Denmark during Period IV. A Jutland tribe mainly concentrated in North and Middle Jutland, and a tribe on the islands. The question is whether it is not too much of a simplification to divide Denmark into two tribes, as the artefacts reflect a more complicated situation. However, the idea of several regions having existed in the Danish area – individual cultural units with mutual contact – is not unlikely. The two wealth centres of Boeslunde in Western Zealand and Voldtofte on Southwest Funen may represent two independent regions in Denmark, to which the North- and Central Jutland period may be added as a third region due to its special artefacts. We thus get at least three regions in Denmark during the Late Bronze Age. In period V, we no longer have the same difference between South Scandinavian artefacts, and the distinctive character of the Jutland material seems to disappear. This does not mean that North and Central Jutland loose influence – on the contrary. However, we see a certain uniformity within the Nordic artefact material from Period V. In Period IV, North and Central Jutland was a region where people expressed their affiliation through the way they chose to decorate themselves. The area was probably inhabited by an independent people or tribe – assumed on the grounds that this is the place in Late Bronze Age Scandinavia where the find material mostly seems to reflect a region with unique artefact types expressing individual cultural traditions and a social identity. Jeanette Varberg Institut for Antropologi, Arkæologi og Lingvistik, Aarhus Universitet Translated by Annette Lerche Trolle